Developing critical thinking through eportfolio based learning: an exploration of the experiences of non-traditional online distance learners - FARRELL, ORNA (Trinity College Dublin. School of Education. Discipline of Education, 2019)
This doctoral study explores the nature of the learning experience with an eportfolio and whether it enhances the development of critical thinking among online distance learners. The project adopts a case study approach, following twenty-four online distance learners over the course of one academic year. The study focuses on the case of the learner experience of eportfolio based learning and the process of developing critical thinking. The research question for the study is: Can eportfolios enhance the nature of the learning experience and the development of critical thinking among online distance learners? Data were generated using the participant eportfolio entries and two-time semi structured interviews. The participants were interviewed with their eportfolio, written, visual and physical artefacts from the participant?s eportfolio were used as stimulus during the interviews. The analytical approach for the study was thematic analysis, a data led approach following the Braun & Clarke (2006) six phases of thematic analysis. The findings were presented into five themes, which demonstrated the multifaceted nature of learning experiences with an eportfolio and its relationship with the development of critical thinking for online distance learners. The themes were; being an online distance learner, the experience of learning with an eportfolio, my approach to learning, thinking critically in my eportfolio, the sociology discipline context. Findings indicate that learning with an eportfolio can enhance the nature of the learning experience by providing learners with a personal space to evaluate their own learning, to process their thoughts and experiences and to document their lives and learning in an authentic and meaningful way. In addition, the findings suggest that learning with an eportfolio can enhance the development of critical thinking skills and dispositions within a disciplinary context.
APPROVED
Keywords: critical thinking; eportfolio; online distance learners; sociology